Deworming Coverage and its Predictors among Ethiopian Children Aged 24 to 59 Months: Further Analysis of EDHS 2016 Data Set - Getahun Fentaw Mulaw BSc, MPH; Fentaw Wassie Feleke BSc, MSc; Seada Seid Ahmed BSc, MSc; Juhar Admama Bamud BSc, MSc (SAGE Publishing, 2021)
Intestinal parasitic infections are the major public health problem globally, mostly in developing countries. World Health Organization recommends deworming to all at-risk people living in endemic areas as a prevention or intervention strategy. Therefore this study aimed to assess the deworming coverage and its predictors among Ethiopian children aged 24-59 months. The study analyzed retrospectively cross-sectional data on a weighted sample of 5,948 children aged 24-59 months nested within 645 clusters after extracting from the Ethiopian Demographic health survey. Bivariable and multivariable logistic regression was employed to assess the association of variables. Predictors at p-value < 0.25 were entered into the multivariable logistic regression model, and statistical significance was declared at P-value < 0.05. In this study, the prevalence of maternal reported deworming supplements among children aged 24-59 months was 15.1%. Predictive variables significantly associated with deworming supplementation include maternal media exposure, maternal control of household healthcare decisions, institutional healthcare delivery, and child vitamin-A supplementation. Having history of a diarrheal disease, maternal and paternal education, and family size were also statistically significant predictors of deworming supplements. Therefore, deworming supplementation among children is low. Maternal education and employment, paternal education, family size, decision-making process, maternal media exposure, place of delivery, vitamin-A supplementation, and a having history of diarrhea were predictors of deworming supplements. Multifaceted interventions aimed at those predictors should be given emphasis.